Conceptual design of a large-scale floating offshore vertical axis wind turbine. (December 2017) - Hand, Brian; Cashman, Andrew
Abstract: Large-scale floating vertical axis wind turbines (VAWTs) are an attractive and economical solution to harness superior offshore wind resources in deep water locations. This paper presents the conceptual design of a VAWT for this application using a developed aerodynamic modelling strategy. A comprehensive examination of several critical VAWT design parameters was undertaken which included the turbine solidity, blade number, blade aspect ratio and non-prismatic strut design. This study identified a low solidity turbine (σ = 0.263) gave the best aerodynamic performance, while a two-bladed VAWT design is recommended. The results also indicated a blade aspect ratio in the range 10 ≥ H/c ≥ 20 gives favorable performance. Finally, the geometrical details and operating specifications for a 5 MW VAWT design are presented.